2015
DOI: 10.1021/jacs.5b07924
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum-Carbide-Modified Nitrogen-Doped Carbon Vesicle Encapsulating Nickel Nanoparticles: A Highly Efficient, Low-Cost Catalyst for Hydrogen Evolution Reaction

Abstract: Despite being promising substitutes for noble metal catalysts used in hydrogen evolution reaction (HER), the nonprecious metal catalysts (NPMCs) based on inexpensive and earth-abundant 3d transition metals (TMs) are still practically unfeasible due mainly to unsatisfactory activity and durability. Herein, a highly active and stable catalyst for HER has been developed on the basis of molybdenum-carbide-modified N-doped carbon vesicle encapsulating Ni nanoparticles (MoxC-Ni@NCV). This MoxC-Ni@NCV material was sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
268
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(278 citation statements)
references
References 56 publications
10
268
0
Order By: Relevance
“…However, our results showed that the nitrogen content in the studied catalysts had little effect on the HER activity, although the nitrogen content in nitrogen-doped carbon was described to be crucial to the HER activity. 50,51 Therefore, we reasoned that the nitrogen dopant is not the main reason for the enhanced HER activity of Ni/Mo 2 C-PC (Fig. S12, ESI†).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our results showed that the nitrogen content in the studied catalysts had little effect on the HER activity, although the nitrogen content in nitrogen-doped carbon was described to be crucial to the HER activity. 50,51 Therefore, we reasoned that the nitrogen dopant is not the main reason for the enhanced HER activity of Ni/Mo 2 C-PC (Fig. S12, ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…2327 In view of the above considerations, chemically coupling Ni with Mo 2 C is supposed to result in an improved HER catalytic activity. 28 Moreover, such combination is also likely to realize outstanding OER performance owing to the presence of OER-active Ni. 2932 This catalyst design eventually will lead to a new bifunctional catalyst for efficient overall water splitting application, which is highly desirable for electrolyser development.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] In particular, due to their porous structures with high surface areas, MOFs are ideal sacrificial templates to derive into various porous active materials, such as carbonaceous materials, metal oxides, and metal phosphides. [11][12][13][14][15][16][17][18][19] For example, a novel hollowed cubic NiS nanoframe electrode was achieved by anion exchange of a Ni-Co MOF with S 2− ions, which demonstrated enhanced capacitive performance for electrochemical capacitors. [11][12][13][14][15][16][17][18][19] For example, a novel hollowed cubic NiS nanoframe electrode was achieved by anion exchange of a Ni-Co MOF with S 2− ions, which demonstrated enhanced capacitive performance for electrochemical capacitors.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] A critical element to vanquish this challenge is the design of satisfactory electrocatalysts with low overpotential, a small Tafel slope, and a large exchange current to drive hydrogen evolution. 8 Illuminated by the burgeoning exploratory research, the economical and abundant metal dichalcogenides, [9][10][11][12][13][14][15] nitrides, [16][17][18] phosphides, [19][20][21][22][23][24] etc.…”
Section: ■ Introductionmentioning
confidence: 99%